Addressing psychological resilience and its determinants among university students during the COVID-19 pandemic: a three-wave longitudinal study in Shandong Province, China - Pan, Lutong; Zhao, Jingjing; Pang, Mingli; Wang, Jieru; Zhou, Yue; Chen, Rui; Liu, Hui; Xu, Xixing; Su, Baochen; Nie, Limei; Zhao, Jiajia; Li, Shixue; et al. (BMC psychiatry, 2024)
The relationship between public health emergencies and psychological distress had been well known, yet none research had been conducted on the trend in psychological resilience and its longitudinal determinants during the pandemic. This study aimed to explore the changes of psychological resilience of university students during COVID-19 pandemic, and further clarify the longitudinal relationship between family factors, mental health, social mentality and psychological resilience. Questionnaires were distributed to students from five universities in Shandong Province, China during the COVID-19. A total of 1635 students were finally included in this three-wave follow-up study using stratified random sampling method. Mental health was assessed by Depression Anxiety Stress Scale, social mentality was measured by the Bi-Dimensional Structure Questionnaire of Social Mentality, psychological resilience was evaluated by the Chinese version of the Psychological Resilience Scale. Repeated-measures analysis of variance was used to analyze the longitudinal changes of psychological resilience, generalized estimating equation (GEE) was conducted to estimate the determinants of psychological resilience. Psychological resilience changed from 28.37 in Wave 1, 29.10 in Wave 2, and 29.15 in Wave 3 among the university students. The students who majored in Art (β = 0.872, P = 0.032), parents (mother β = 0.546, P = 0.035; father β = 0.718, P = 0.012) had a greater influence on children's personality, and positive social mentality (β = 5.725, P < 0.001) were more likely to report a higher psychological resilience. Being female (β=-0.932, P < 0.001), not being a student leader (β=-0.911, P < 0.001), being anxious (β=-1.845, P < 0.001) and depressed (β=-1.846, P < 0.001), and negative social mentality (β=-0.803, P < 0.001) were less likely to report a higher psychological resilience. The psychological resilience of the university students in Shandong Province, China increased significantly from Wave 1 to Wave 3 during the COVID-19 pandemic. Majoring in Art, parents having a greater influence on children's personality, better mental health, positive social mentality were more likely to report a higher psychological resilience, while female, not student leader, worse mental health, and negative social mentality were less likely to report a higher the psychological resilience.